2001
DOI: 10.1034/j.1600-0528.2001.029001009.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk group assessment of oral precancer attached to X-ray lung-screening examinations

Abstract: The mortality rate of oral tumours in Hungary, as in some other countries, is increasing. In order to assess risk groups for oral cancer and precancer, oral examinations were carried out as part of the X-ray screenings for lung cancer in the 3rd district of Budapest, Hungary. There were 5,034 adults who participated voluntarily in these investigations. After completing a questionnaire with 23 questions, a short oral examination was performed. Males comprised 57.7% of the group, and the age-distribution among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…A total of 16 OC/pre‐cancer screening studies conducted in Europe over a span of three decades were retrieved from our searches . The first of the screening programmes was conducted in 1973–1974 in Sweden (published in 1987 following a re‐evaluation) and was the largest reported so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 OC/pre‐cancer screening studies conducted in Europe over a span of three decades were retrieved from our searches . The first of the screening programmes was conducted in 1973–1974 in Sweden (published in 1987 following a re‐evaluation) and was the largest reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…Dombi et al. conducted a multiphasic screening programme for those who were willing to accept oral examinations whilst attending a lung‐screening station in the 3rd District of Budapest. Screening examinations were performed by general dental practitioners on 1 day per week over an undefined time period.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, all of the leukoplakia lesions recorded were in males and smokers. Axéll (14), in Sweden, found leukoplakia in 3.6% of cases; Reichart and Kohn (23), in Berlin, found that 0.9% showed oral leukoplakia and 0.1% smoker's palate; Banoczy's group (24) from Hungary reported 3.3% with oral leukoplakia. Field et al.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates approximately 15% of the world's malignancies are associated with chronic inflammation [39, 40]. In head and neck carcinogenesis, chronic inflammation is an accompanying feature of dysplastic lesions and at least 75% of leukoplakia lesions are associated with smoking [41–44].…”
Section: Introductionmentioning
confidence: 99%